Comparison of Nedaplatin- and Cisplatin-Based Concurrent Chemoradiotherapy in Locally Advanced Cervical Cancer Patients: A Propensity Score Analysis. Issue 5 (June 2018) - Li, Ping; Zhang, Rui; Nie, Zhihua; Long, Mengjuan; Zhang, Gong; Fu, Zhenming
Abstract : Purpose: The aim of this study was to evaluate the efficacy of using nedaplatin to replace cisplatin for concurrent chemoradiotherapy (CCRT) in patients with newly diagnosed locally advanced cervical cancer. Methods: The medical records of 155 patients with cervical cancer who had undergone CCRT with cisplatin (n = 85) or nedaplatin (n = 70) between January 2012 and January 2017 were retrospectively reviewed. Propensity score analysis with 1:1 matching with the nearest neighbor matching method was performed to assess response rates, progression-free survival, overall survival, and toxicity between 2 groups. Results: Propensity score matching identified 63 patients in each group. After matching, compared with patients treated with cisplatin-based concurrent chemoradiotherapy (CisRT), we found that patients treated with nedaplatin-based concurrent chemoradiotherapy (NedaRT) had a significant higher recurrence rate (25.4% vs 42.9%; P = 0.04). In addition, the 3-year progression-free survival rate for NedaRT group was also worse than that for the CisRT group (52.2% vs 63.4%, P = 0.03). There was no difference in the overall response rates between the CisRT and NedaRT groups (87.3% and 90.5%, respectively; P = 0.57). The rates of 3-year overall survival and grades 3 to 4 toxicities were similar between the 2 groups. Conclusions: The clinical outcome of this cohort of patients with locally advanced cervical cancer treated with CCRT did in no way provide support for the use of nedaplatin in place of cisplatin in chemoradiation and demonstrated no equivalence of the 2 drugs. Cautions should be taken for the replacement among platinum complexes in cancer treatment.